To determine which of the ordered pairs is a solution for the equation \( y = 4z + 2 \), we will substitute the \( z \) value from each pair into the equation and see if the resulting \( y \) value matches the \( y \) given in the pair.
-
For the pair \((-2, -6)\):
- Substitute \( z = -2 \): \[ y = 4(-2) + 2 = -8 + 2 = -6 \]
- This matches the \( y \) value of -6, so \((-2, -6)\) is a solution.
-
For the pair \((-1, 0)\):
- Substitute \( z = -1 \): \[ y = 4(-1) + 2 = -4 + 2 = -2 \]
- This does not match the \( y \) value of 0, so \((-1, 0)\) is not a solution.
-
For the pair \((-2, 6)\):
- Substitute \( z = -2 \): \[ y = 4(-2) + 2 = -8 + 2 = -6 \]
- This does not match the \( y \) value of 6, so \((-2, 6)\) is not a solution.
-
For the pair \((0, 2)\):
- Substitute \( z = 0 \): \[ y = 4(0) + 2 = 0 + 2 = 2 \]
- This matches the \( y \) value of 2, so \((0, 2)\) is a solution.
Summary:
- Solutions: \((-2, -6)\), \((0, 2)\)
- Not solutions: \((-1, 0)\), \((-2, 6)\)